(untitled) (Altre Modernità, 2010)
This article tries to place and characterize the latinoamerican political discourse. The analyses of some cases (Fidel Castro, Hugo Chávez, Fernando Lugo, Rafael Correa, Evo Morales and Luiz Inácio Lula da Silva) contain verbal and gestual elements, and the persuasive consequences of political discourse.